Berthing characteristics and the behaviour of the oil terminal of Leixões Harbour, Portugal - F. Veloso Gomes (2005)
Larger depth requirements for large tankers together with security reasons necessitate the establishment of oil terminals located in areas more exposed to adverse sea state conditions, conditioning terminal operations' efficiency and putting severe demands on fender and mooring systems. This paper describes the characteristics and behaviour of the berth "A" of Leixoes Harbour oil terminal which is, from the three berths that compose the oil terminal, the one that has the most significant hydrodynamic and operational problems, due to its exposed location despite the adjacent breakwater. The present conditions of berth "A" causes an obvious cost, as well as environmental and safety risks to the port authority, and for that reason this berth has been the subject Of Studies with the aim of improving its operational and security conditions. This paper will also present an overall overview of some conclusions of a recent Study that has been carried out.